Tingkat Kinerja Penyuluh pada Kelompok Tani Padi Sawah di Desa Bumi Raya Kecamatan Andoolo Kabupaten Konawe Selatan - Sutriani, Ni Wayan; Arimbawa, Putu; Abdullah, Sukmawati (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2019)
This is an improvement in the performance of extension agents to the lowland rice farmers in Bumi Raya Village, Andoolo District, Konawe District in the south. Determination of the sample is done by Purposive method, Total observation sample 11 respondents consist of 10 respondents farmer groups and 1 agricultural extension agent. This data is by using Interval Analysis. Based on the description of the results of the study, the following conclusions can be drawn: the results of the study indicate that the level of performance of agricultural extension workers in the village of Bumi Raya, Andoolo Subdistrict, South Konawe Regency is categorized as high. From the results of the analysis of the performance of agricultural extension workers showing indicators of the Development Aspect delivered by the instructor had satisfied the farmer groups. In providing counseling to farmer groups, extension workers should not only visit senior farmer groups (primary level) but also beginner and middle farmer groups, so that novice farmer groups can learn more from agricultural extension agents as a source of information and to avoid misunderstandings between farmer groups. In addition, it is expected that the instructor will make a clear plan according to the needs of the farmer, evaluate the farmer groups, not only to the chairman or management but to the members of the farmer group.